Stepping into the enigma: Teaching international business 4.0 - Danko, Taras (My University, 2021)
As more and more evidence demonstrates the abrupt and radical change of the international business realities caused by the fourth industrial revolution, it’s time to accommodate these new developments into the learning experiences of future international managers. To gain resiliency and remain competitive, international companies learn and adopt new emerging managerial practices of International Business 4.0. In their turn, in order to remain relevant in the area of business and management education, universities need to upskill, to provide proper learning opportunities for the next generation of managers who are preparing for the implications of International Business 4.0. This must be done by rethinking what are the appropriate learning outcomes and methods that meet the emerging requirements of transforming business organizations.
Keywords: International business; International business 4.0; Fourth industrial revolution; Industry 4.0; University 4.0